2018
DOI: 10.3390/children5070083
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Executive Functioning and Academic Achievement in the Academic Self-Concept of Children and Adolescents Referred for Neuropsychological Assessment

Abstract: The current study evaluated a model of youth academic self-concept which incorporates practical executive functioning behaviors and academic achievement. Though greater academic achievement has been linked to both positive self-concept and better executive functioning, these constructs have not been examined simultaneously. It was hypothesized that academic achievement would mediate the association between problems with executive functioning and academic self-concept such that youth with more problems with exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…Difficulties in EF such as difficulties in organizing, planning, working memory, monitoring, and inhibition, complicate crucial cognitive and social development making it challenging to children with ADHD to adapt to the classroom environment. At the same time, as a result of cycles of frequent academic failures and subsequent criticism, the self-esteem of children with ADHD is likely to be reduced (Bailey et al, 2018). In the present study, we examined whether therapeutic horseback riding, paired with medication, is an effective treatment method to cultivate children’s EFs and restore their self-esteem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Difficulties in EF such as difficulties in organizing, planning, working memory, monitoring, and inhibition, complicate crucial cognitive and social development making it challenging to children with ADHD to adapt to the classroom environment. At the same time, as a result of cycles of frequent academic failures and subsequent criticism, the self-esteem of children with ADHD is likely to be reduced (Bailey et al, 2018). In the present study, we examined whether therapeutic horseback riding, paired with medication, is an effective treatment method to cultivate children’s EFs and restore their self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…The term EFs refers to the cognitive mechanisms that are responsible for self-regulation in cognitive, behavioral, and emotional functioning including planning, working memory, cognitive shifting, sustaining effort, inhibition, self-monitoring, self-regulation, and initiation (Barkley, 2006; Graziano et al, 2011). EFs difficulties have lifelong implications for behavioral, social, emotional, and adaptive problems, including academic challenges in childhood (APA, 2013; Bailey et al, 2018; Barkley, 2014; Tarver et al, 2014).…”
Section: Efsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent experience with ACEs have resulted in observed behavior in school-age students, such as lack of curiosity, low self-esteem, self-sabotaging behaviors, difficulties in regulation, memory impairment, inability to overcome failure, maladaptive self-soothing behaviors, and hyperactivity (Cook et al, 2005;Evans & Wachs, 2010;Loman, & Gunnar, 2010;Perry, 2009;Siegel & Bryson;2015;Wiik, Loman, Frenn, Pollak, & Gunnar, 2011). Conversely, multiple studies have found a direct correlation between students' EF skills and their success on academic tasks (Bailey, Andrzejewski, Greif, Svingos, & Heaton, 2018;Gumora G., Arsenio 2002;Latzman, Elkovitch, Young, Anna, & Clark, 2010).…”
Section: Theoretical Framework Adverse Childhood Experiences and Execmentioning
confidence: 92%
“…Moreover, other studies have found that, according to teachers, children with ASD show greater dysfunction in social participation and praxis (4). Likewise, recent studies have stated that praxis and social participation, along with difficulties in proprioception, seem to be more characteristic of ADHD, whereas social difficulties seem to be typical of ASD, which could be related to contextual hyperselectivity, as an inherent characteristic of ASD (80).…”
Section: Description Of the Epyfei-escolar Questionnairementioning
confidence: 98%